(3TQM eSGFd Mfjfs - (3CHh GdbGSe YHO GdQMef Hf Ydj Hf CMeO Hf CHi UGOb GdfjSGHhQis; (3Mfjf Hf ESMGb GdYHGOqj, CHh RjO,J (B260 (3g` s ((3LeGd Hf eMeO Hf GdMSjf s)
(3ChdgG (B:s
(3GdMeO ddg MeO eYJQa HGdGAg bGd GdTjN GdMcje CHh GdbGSe Cf CQHGH GdeYQaI HUfGYI GdWH bO JhGWFhG Ydi Cf GdQGZH ai gPG GdYde jLH Cf jaJJM JYdeg HcJGH GdeSGFd dMfjf Hf GSMGb s
(3BNQgG (B:s
(3hEfi deG QCjJ MGd gPG GdYde Ydi gPg GdUhQI hhLOJ cd ef jQjO GdEdgGe Hg jJMOi GdfXQ ai gPG GdcJGH Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1668s
Keywords: (3GdWHs